Rancang Bangun Mobile Commerce Untuk Pencatatan Penjualan Sayur Organik Menggunakan GCM - Robert William Ruhulessin; Hindriyanto Dwi Purnomo; Radius Tanone; Purwanto Purwanto; Teguh Indra Bayu (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2017)
Organic vegetable trade industry Sayur Organik Merbabu in the Kopeng in Salatiga in the recording sales still use a paper and kept using spreadsheets so inefficient in processing the selling data .The initial underlying problem doing design application mobile commerce to recording sales consisting of two applications for buyers that allows buyers can buy a vegetable online and business owners as an administrator managing data sales .The method used in this research is the approach technique , where the final result expected is a prototype. The results are two application application of the recording a sale that may used to record the process of trading online and offline indicated for an administrator, then application of vegetable online organic devoted to buyers.